2016
DOI: 10.1097/mph.0000000000000583
|View full text |Cite
|
Sign up to set email alerts
|

Phase I and Phase II Objective Response Rates are Correlated in Pediatric Cancer Trials: An Argument for Better Clinical Trial Efficiency

Abstract: While many phase I trials report tumor response, formal analysis of efficacy is deferred to phase II. We reviewed paired phase I and II pediatric oncology trials to ascertain the relationship between phase I and II objective response (OR%). Single-agent phase I trials were paired with corresponding phase II trials (comparable study drug, dosing schedule, and population). Phase I trials without efficacy data or a matching phase II trial were excluded. OR% was tabulated for all trials, and phase II authors' subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…Notably, half the studies included in this review tested drugs as single agents. The necessity to use combination therapies to improve cure rates in both child and adult cancers has been theorized for decades . There may, however, be reasons trialists opt for single‐agent studies, including the reticence of pharmaceutical companies to work with competitors and difficulty in understanding which agents are active when using combination therapies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, half the studies included in this review tested drugs as single agents. The necessity to use combination therapies to improve cure rates in both child and adult cancers has been theorized for decades . There may, however, be reasons trialists opt for single‐agent studies, including the reticence of pharmaceutical companies to work with competitors and difficulty in understanding which agents are active when using combination therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, there may be clinical factors that predict which trial may be successful. Phase I response rates have recently been found to significantly correlate with subsequent phase II response . However, it is unknown whether a trial supported by prior adult or pediatric early‐phase studies will have a higher possibility of attaining clinical success compared with trials supported by preclinical research.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, a recent systematic review compared phase I and phase II trial efficacy results and found that a higher phase I ORR correlated with greater probability of a positive phase II outcome. Most of the agents considered in that study were cytotoxic . Upon closer consideration of the solid tumor trials involving targeted drugs included in that study, four of the five paired studies showed no objective responses in the phase I study but did show disease responses in the subsequent phase II study .…”
Section: Discussionmentioning
confidence: 97%
“…159 Upon closer consideration of the solid tumor trials involving targeted drugs included in that study, four of the five paired studies showed no objective responses in the phase I study but did show disease responses in the subsequent phase II study. 159 Furthermore, based on experiences in adults, it will become increasingly important to incorporate screening for relevant molecular aberrations in eligibility criteria of, even early-phase, pediatric targeted agent trials to maximize potential benefit to individual enrolled patients. Additionally, it is critical to consider toxicity profiles of new targeted drugs carefully, as they often have unique nonhematologic side effects related to inhibition of molecular pathways in normal cells and may have particular significance for children who are still undergoing development.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation